2005
DOI: 10.1161/circulationaha.104.527549
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Spironolactone Therapy for Older Patients With Heart Failure and Left Ventricular Systolic Dysfunction in the United States, 1998–2001

Abstract: Background-Concerns have been raised about the appropriateness of spironolactone use in some patients with heart failure. We studied the adoption of spironolactone therapy after publication of the Randomized Aldactone Evaluation Study (RALES) in national cohorts of older patients hospitalized for heart failure. Methods and Results-This is a study of serial cross-sectional samples of Medicare beneficiaries Ն65 years old discharged after hospitalization for the primary diagnosis of heart failure and with left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 27 publications
1
71
1
Order By: Relevance
“…Risk of renal side effects and hyperkalemia in older patients could explain low persistence for treatment with RASi or spironolactone, as well as for combination treatment with RASi and spironolactone in this population. 12 Notably, an increased number of concomitant medications was associated with persistence of treatment, an important finding because treatment of HF often involves polypharmacy. Also, increased severity of HF did not worsen persistence, in contrast to studies that demonstrated risk-treatment mismatch in the pharmacotherapy of HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk of renal side effects and hyperkalemia in older patients could explain low persistence for treatment with RASi or spironolactone, as well as for combination treatment with RASi and spironolactone in this population. 12 Notably, an increased number of concomitant medications was associated with persistence of treatment, an important finding because treatment of HF often involves polypharmacy. Also, increased severity of HF did not worsen persistence, in contrast to studies that demonstrated risk-treatment mismatch in the pharmacotherapy of HF.…”
Section: Discussionmentioning
confidence: 99%
“…In the Randomized Aldactone Evaluation Study (RALES), spironolactone treatment reduced mortality in severe HF by 30%. 11 But later studies have demonstrated increased risk of hyperkalemia 12,19 and increased mortality associated with spironolactone treatment in chronic HF, 25 which could explain why the benefit of spironolactone treatment is not reflected in increased mortality in nonpersistent patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although spironolactone is generally well tolerated, hyperkalemia is a potentially life-threatening adverse effect of the drug in clinical practice. [3][4][5] Strategies for mitigating the risk of serious hyperkalemia include cautious dosing of spironolactone, close monitoring of electrolyte levels and avoidance of other drugs that cause hyperkalemia.…”
mentioning
confidence: 99%
“…Accordingly, the writing committee felt that initiation of aldosterone blockade as a layered therapy (in patients treated with ACEI and beta-blockers) may be most appropriate in the early postdischarge setting. Finally, the writing committee also had some concerns about recent evidence in regard to the use of aldosterone blockade in patients with contraindications to this therapy, 60 which in some cases puts patients at risk for hyperkalemia. The committee believed that, in addition to an outpatient measure for the use of aldosterone antagonists, a parallel measure of inappropriate use may be warranted.…”
Section: Aldosterone Blockadementioning
confidence: 99%